Fractured Modernity: America Confronts Modern Times, 1890s to 1940s - Welskopp, Thomas; Lessoff, Alan (Schriften des Historischen Kollegs, 2016)
The ten essays in this volume deal with the debates and conflicts about modernity in a period of American history when the tensions and strains caused by seemingly unrestrained change and the reactions to it were particularly severe and tangible. Partly concentrating on the margins or dark underworlds of modernity, such as racism and violence, partly focusing on the allegedly unlimited space to negotiate and create social order from scratch, the contributions to this volume show that, and discuss why, modernity was an issue in contemporary United States which seemed to have been even more hotly contested than in Europe at the same time, albeit sometimes in terms of “Americanism” rather than “modernism”. In this book, European scholars of the United States apply variations on the transnational discourse on modernity to unexpected dimensions of U.S. history, making this volume a fascinating example of the present-day enterprise of internationalizing American studies.